2014
DOI: 10.1242/dev.098459
|View full text |Cite
|
Sign up to set email alerts
|

Macrophages modulate adult zebrafish tail fin regeneration

Abstract: Neutrophils and macrophages, as key mediators of inflammation, have defined functionally important roles in mammalian tissue repair. Although recent evidence suggests that similar cells exist in zebrafish and also migrate to sites of injury in larvae, whether these cells are functionally important for wound healing or regeneration in adult zebrafish is unknown. To begin to address these questions, we first tracked neutrophils (lyzC+, mpo+) and macrophages (mpeg1+) in adult zebrafish following amputation of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

26
316
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 309 publications
(343 citation statements)
references
References 69 publications
26
316
0
1
Order By: Relevance
“…Modulation of macrophages attenuates regeneration in salamander limb, zebrafish appendage and neonatal heart regeneration (Aurora et al, 2014;Godwin et al, 2013;Petrie et al, 2014). Previous work on miR-101a in the mammalian heart suggests that fosab is enriched in cardiac fibroblasts and not CMs (Pan et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Modulation of macrophages attenuates regeneration in salamander limb, zebrafish appendage and neonatal heart regeneration (Aurora et al, 2014;Godwin et al, 2013;Petrie et al, 2014). Previous work on miR-101a in the mammalian heart suggests that fosab is enriched in cardiac fibroblasts and not CMs (Pan et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…This does not rule out the involvement of other hematopoietic cells and endothelial cells for the survival of regenerative cells, but in accordance with our result, a number of reports have suggested the important relationship between myeloid lineage cells and regeneration. A recent study by Petrie et al (2014) showed that ablation of macrophages during adult fin regeneration reduces blastema cell proliferation and causes abnormal regeneration. Although these studies did not inspect apoptosis during regeneration, the decrease of survival factor could be a cause of the regeneration defects observed in these studies.…”
Section: Discussionmentioning
confidence: 99%
“…Recruitment of macrophages to the vicinity of apoptotic cells is also observed in vertebrates. In the zebrafish fin, macrophages are recruited to the amputation site and required for proliferation in the early stages of tissue outgrowth by activating Wnt signaling [75]. Similarly, macrophages are recruited to injured mouse and chick cochlea and utricle and produce TNFa to promote cell proliferation [76][77][78].…”
Section: Identifying New Molecules/pathways Important For Hair Cell Rmentioning
confidence: 99%